Bibliometric Insights into Pearl Millet-based Cropping Systems and Soil Health Research: A Comprehensive Analysis (2000–2023): Pearl–millet-based cropping system and soil health - Chaudhary, Amresh; Meena, M.C.; Bana, RS; Rai, A.K.; Basak, N; Kumar, Jitendra (Journal of Soil Salinity and Water Quality, 2025)
This article presents a comprehensive bibliometric analysis of studies conducted on pearl millet–based cropping systems and soil health from 2000 to 2023, utilizing the Scopus database. Pearl millet, a significant cereal crop globally, is known for its resilience in arid and semi–arid conditions. The cultivation of pearl millet spans over 30 million hectares worldwide, with India contributing significantly to its acreage. The study examines the impact of pearl millet production in rainfed and arid regions on soil health under conservation agriculture (CA) practices. The bibliometric analysis employs rigorous methodologies, including Bradford’s Law, fractionalized articles, and thematic mapping. It reveals the evolution of scientific output, citation patterns, and collaborative networks. Findings indicate a steady growth in scientific production related to pearl millet research, with a notable surge in recent years. The average citations per year exhibit fluctuating trends, emphasizing the need for continued exploration. We found that there is limited research in the area of pearl millet–based cropping system in relation with soil health. Brazil, USA and India are the top three countries conducting research on this area. CA under degraded soils with pearl millet is still unexplored area of research. It also found that in last one decade (2011–2022), scientists are working in this area has been increased as per number of documents published as citations received during this period on the given topic. Pearl millet-based cropping systems, integrated with CA practices such as zero tillage, residue incorporation, and deficit irrigation, offer a sustainable and climate-resilient solution for addressing soil salinity challenges while enhancing soil health, water use efficiency, and nutritional security in arid and semi-arid regions. The study concludes by identifying research gaps, emphasizing the need for further investigations into the advantages of pearl millet–based cropping systems, their impact on soil health, and the development of production systems for degraded soils. Despite limitations related to the temporal scope, database constraints, and language bias, the study contributes valuable insights into the dynamic field of pearl millet research, guiding future endeavours and fostering collaboration among researchers, policymakers, and practitioners.